Comparison between Base Metals and Platinum Group Metals in Nitrogen, M Codoped TiO2 (M = Fe, Cu, Pd, Os) for Photocatalytic Removal of an Organic Dye in Water. (27th October 2014) - Kuvarega, Alex T.; Krause, Rui W. M.; Mamba, Bhekie B.
Abstract : The photocatalytic performance of a number of nonmetal and metal codoped TiO2 for the degradation of eosin yellow under simulated solar radiation was investigated. The synthesised materials were characterised by FTIR, Raman spectroscopy, XRD, DRUV-Vis, SEM, and TEM. The N, metal codoped TiO2 containing 0.5 wt.% of the metal consisted mainly of the anatase phase, with a particle size range of 15–28 nm. The particles were largely spherical and shifted the absorption edge well into the visible region. Band gap reduction was more pronounced for the N, PGM codoped TiO2 compared to N, base metal codoped samples. Codoping led to an enhancement in the photocatalytic activity of the materials for the degradation of eosin yellow. N, Pd codoped TiO2 was the most effective photocatalyst (99.9% dye removal) while N, Cu codoped TiO2 showed the least activity (25.5% removal). The mechanism for the photocatalytic enhancement was proposed on the basis of formation of an electron deficient Schottky barrier at the semiconductor-metal interface, which acts as an electron sink and thus retards electron-hole recombination. It was shown that the ability of the photocatalyst to degrade the dye depends on the nature and type of the metal dopant in the codoped TiO2 system.